Ministry of Investment Decree No. 45 of the Year 2015 Amending Some Provisions of the Executive Regulations of the Capital Market Law Issued as per Decree of the Minister of Economy and Foreign Trade No. 135 of the Year 1993 = وزارة الاستثمار قرار رقم 45 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون سوق رأس المال الصادر بقرار وزير الاقتصاد والتجارة الخارجية رقم 135 لسنة 1993 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic